An investigation of the psychopharmacology of timing behavior in the rat - Asgari-Mobaraké, Karim (2006)
Interval timing behaviour refers to the ability of animals and humans to adapt their behaviour to temporal regularities in their environments. Two important classes of interval timing behaviour are temporal discrimination (discriminating between the durations of external events) and temporal differentiation (behavioural adaptation during an ongoing interval). It has been known for many years that drugs that affect central dopaminergic function can alter both forms of timing behaviour. More recently, evidence has been accumulated which shows that manipulation of central 5-hydroxytryptaminergic (5-HTergic) function can also influence interval timing behaviour. The experiments described in this thesis examined the effects of drugs acting at some subtypes of 5-HT receptors on temporal discrimination and temporal differentiation in the rat.